Study of Molar Refraction and Polarizability Constant of 2’-Hydroxy-5’-Methyl-4-Methoxy Chalcone in Different Percentage of Acetone-Water Mixture - Burghate, A.S.; Agarwal, P.B.; Quazi, S.W.; Narwade, M.L. (Asian Journal of Chemistry, 2010)
The refractive indices of acetone-water and 2'-hydroxy-5'methyl- 4-methoxy chalcone-acetone-water in different percentages of acetone-water mixtures were measured by Abbe's refractometer at 27 ± 0.1 °C. The data obtained is utilised to calculate molar -refraction and polarizability constant and estimate the nature of dipole.